HUBUNGAN JENIS KELAMIN, PENGETAHUAN, DAN POLA MAKAN DENGAN STATUS GIZI REMAJA DI SMPN 6 MEUREUBO, KABUPATEN ACEH BARAT TAHUN 2025 - Mutia Satriani, Cut; Khairunnas (Jurnal Biogenerasi, 2025)
This study aimed to analyze the relationship between gender, knowledge, and eating patterns with the nutritional status of students at SMP Negeri 6 Meureubo, West Aceh Regency, in 2025. Using a quantitative cross-sectional design, the study involved 61 seventh- and eighth-grade students selected through random sampling. Data were analyzed using the Chi-Square test. The results revealed no significant relationship between gender and nutritional status (p = 0.746), suggesting that gender does not influence students’ nutritional conditions. However, a significant relationship was found between nutritional knowledge and nutritional status (p = 0.014), and between dietary patterns and nutritional status (p = 0.004). Students with good knowledge and healthy eating habits tended to have normal or ideal nutritional status. These findings indicate that knowledge and eating patterns play a key role in determining adolescent nutrition, while gender does not. Therefore, interventions should focus on increasing students’ nutritional awareness and encouraging healthy eating habits. Schools are encouraged to integrate nutrition education into the curriculum, provide nutritious food options in canteens, and involve parents in promoting healthy behaviors to foster a healthier and more productive generation of adolescents.